Investigating Industry 4.0, blockchain adoption, and sustainability on Thai finance's operational excellence - Rawin Vongurai (Global Business & Finance Review (GBFR), 2024)
Purpose: This study examines the impact of Industry 4.0, blockchain adoption, and sustainability on operational excellence within the Thai finance sector. Key variables include relative advantage, top management support, openness to use innovation, blockchain technology adoption, industry 4.0 practice, sustainable operation, and operational excellence. Design/methodology/approach: Data was gathered through a survey administered to 278 participants comprising managers, IT experts, and banking and financial professionals, utilizing a quantitative methodology. Prior to data collection, the reliability of the questionnaire was evaluated via a pilot test involving 30 participants, assessing Item-Objective Congruence (IOC) index and reliability using Cronbach's Alpha. Sampling methods encompassed judgmental, convenience, and snowball techniques. Confirmatory Factor Analysis (CFA) and Structural Equation Modeling (SEM) were utilized to validate model fit and test hypotheses. Findings: The study found that relative advantage, top management support, and openness to use innovation sig-nificantly influence blockchain technology adoption. Additionally, blockchain technology adoption and sustainable operation significantly impact operational excellence. However, industry 4.0 practice showed no significant influence on operational excellence. Research limitations/implications: This study sheds light on blockchain adoption and operational excellence but faces limitations. Its context-specific nature may hinder generalization to other sectors or regions, compounded by a limited sample size. Moreover, reliance on self-reported survey data introduces potential response and social desirability biases. Originality/value: The study's insights on Industry 4.0, blockchain adoption, sustainability, and operational ex-cellence in Thai finance benefit practitioners, policymakers, and academics. By intertwining these concepts, it deep-ens understanding of their impact on operational performance. The confirmation of Blockchain Technology Adoption and Sustainable Operation highlights the necessity of strategic investments in these areas.
Keywords: 650; Blockchain Technology Adoption; Industry 4.0 Practice; Sustainable Operation; Operational Excellence; Banking